2012
DOI: 10.1007/s00018-012-0990-9
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of eukaryotic gene expression by the untranslated gene regions and other non-coding elements

Abstract: There is now compelling evidence that the complexity of higher organisms correlates with the relative amount of non-coding RNA rather than the number of protein-coding genes. Previously dismissed as “junk DNA”, it is the non-coding regions of the genome that are responsible for regulation, facilitating complex temporal and spatial gene expression through the combinatorial effect of numerous mechanisms and interactions working together to fine-tune gene expression. The major regions involved in regulation of a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
399
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 491 publications
(411 citation statements)
references
References 199 publications
(285 reference statements)
11
399
0
1
Order By: Relevance
“…These data also demonstrate, for the first time, that the 5 0 UTRdependent modulation of GLA gene expression may vary among different cell types. The expression of alternative 5 0 UTRs represents an evolutionary gain of transcriptional and translational control pathways, allowing tissue-specific expression patterns and expanding the repertoire of expression from a single gene locus (Barrett et al 2012). Although GLA is a housekeeping gene, aGal activity levels vary greatly from organ to organ and in different cell types (Brady et al 1967;von Scheidt et al 1991).…”
Section: Discussionmentioning
confidence: 99%
“…These data also demonstrate, for the first time, that the 5 0 UTRdependent modulation of GLA gene expression may vary among different cell types. The expression of alternative 5 0 UTRs represents an evolutionary gain of transcriptional and translational control pathways, allowing tissue-specific expression patterns and expanding the repertoire of expression from a single gene locus (Barrett et al 2012). Although GLA is a housekeeping gene, aGal activity levels vary greatly from organ to organ and in different cell types (Brady et al 1967;von Scheidt et al 1991).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies reported a correlation between enhancers and chromatin state, including dependence on histone modifications. Enhancers increase the availability of DNA to replication and transcription factors, as well as intensify these processes (Barrett et al 2012). The effect of interactions between enhancers and promoters depends on the distance between them only if it is as significant as several thousand base pairs and then inhibits the enhancers' activity.…”
Section: Enhancer Sequencesmentioning
confidence: 99%
“…The VNTR lies in the 3 0 -UTR, which is located downstream of the protein coding sequence and does not directly affect protein structure. However, the 3 0 -UTR may have a role in influencing posttranscriptional gene expression, for example, through transcript cleavage, mRNA stability, and localization or polyadenylation (Barrett et al, 2012), or remote effects from regulatory regions of other genes (Dekker, 2008).…”
Section: Pharmacogenetic Findingsmentioning
confidence: 99%